Empire Found Racial Identities and Coloniality in Twenty-First-Century Portuguese Popular Cultures - Silva, Daniel (Liverpool University Press, 2022)
Empire Found: Racial Identities and Coloniality in Twenty-First Century Portuguese Popular Cultures examines how the discourses and narratives of Portuguese imperial exceptionalism and Portuguese racial identity, developed during the last centuries of Portuguese settler colonialism continue to inform an array of cultural production and consumption in the four decades since decolonization. By examining a range of contemporary popular cultural production (literature, football, musical production, and celebrity culture) in critical conversation with intellectual production of the nineteenth and twentieth centuries, Empire Found examines how narratives of Portuguese racial hybridity and indeterminacy operate alongside ongoing structures of coloniality and white supremacy in the realms of cultural production. I argue that these implied or overt historical dialogues carried out through cultural production are integral to the very reproduction of the Portuguese nation-state apparatus, as well as its racial structures and claims to whiteness in the wake of decolonization and marginal integration into the European Union.